Top Secret Deportation Operation of the Population of the Baltic Countries (in February 25–August 23, 1949) - Strods, Heinrihs (Genocidas ir rezistencija, 1997)
The annihilation of the Baltic populations after their ‘liberation’ in 1944–1945 belongs to the third, post–war period of communist genocide in the Soviet Union, when the Communist Party, in addition to the so–called "class enemy", began to suspect both "bourgeois" nationalists and entire nations of not being genuinely committed to the USSR. Among such nations were also the ‘Baltic nations’, for whom a special section ‘the Baltics’ was provided in the Gulag documents. The state–organised communist genocide in the third post–war period was increasingly targeted at the inter–republican level under a top-secret codename and a classified date. In the Baltic states, the largest inter–republican communist genocide operation was the top–secret operation of the USSR MGB on 25 March 1949, codenamed ‘Priboj’ (‘Costal Surf’). Until the collapse of the Soviet empire, this operation was only mentioned, and in the last ten years, the lists of deportees have been published and the operation is considered to be a genocide of the Baltic nations, but given that it was orchestrated at the highest level of the state power, the Communist Party, the ways this operation was carried out are, in my opinion, insufficiently revealed due to the unavailability of the primary archival sources.